Relations of the Lithuanian freedom fighters with the west in 1945–1954 and their suppression - Makauskas, Bronius (Genocidas ir rezistencija, 2024)
The article discusses a very important episode of freedom fights – maintenance of Lithuanian anti-Soviet resistance relations with the West, establishment and operation of the communication basis in the territory of South Lithuania and Poland in 1945–1954, seeking to break through the Iron Curtain and to communicate to the democratic world about the consequences of the Soviet occupation in Lithuania and to search for understanding and support in the case of the national resistance against the occupant.
Keywords: Lithuania; partisans; West; Soviet occupation; repressions; Western countries